Effect of foundation rigidity of reinforced concrete MRF-wall on lateral force and drift - Iman Hakamian (مهندسی و مدیریت ساخت)
This study investigates the lateral force distribution and structural drift of moment frames and shear walls under different ground motions with different magnitude. In order to investigation of seismic behavior of concrete structures with dual system including concrete moment resisting frame and concrete shear wall, three 3D 5-story, 10-story and 15-story reinforced concrete moment resistant frames with concrete shear wall were evaluated by linear static and spectral analysis. Material behavior is nonlinear and base condition is flexible. The results of lateral force distribution in cases of fix and flexible-based foundation were presented. In addition, the structural story drift for all 3 type of structures were investigated by nonlinear static and spectral analysis. The results illustrated that the foundation flexibility increases lateral forces in columns as compared to shear walls. As well as this, as the stiffness of springs at the bottom level of foundation decreases, story drift of all structures increases.